KESANTUNAN BERBAHASA PADA MAKSIM KEARIFAN DALAM DEBAT PERTAMA CALON PRESIDEN INDONESIA PERIODE 2024-2029 DI KANAL YOUTUBE METRO TV - Diva Ananda; Sainil Amral; Afif Rofii (Universitas Batanghari, 2025)
This study discusses the forms of tact maxim in politeness strategies during the first Indonesian presidential debate, where the high intensity of communication often challenges the application of politeness principles. The analysis is grounded in pragmatics, focusing on illocutionary speech acts in politeness based on Leech’s (2015) theory of the tact maxim. The main research problem is how the forms of tact maxim appear in the first Indonesian presidential debate for the 2024–2029 period, broadcasted through Metro TV’s YouTube channel. This study employs a qualitative method, with data in the form of quotations from the presidential candidates’ utterances, analyzed using indicators of the tact maxim. The findings reveal that 83 instances of tact maxim were identified in the debate. These results indicate that the application of the tact maxim can foster more conducive political communication, uphold linguistic ethics, and strengthen the speakers’ positive image in the public sphere. This research is expected to serve as a reference in pragmatic studies while contributing to the development of politeness research in political discourse.